Stromal Control of Macrophage Dysfunction in Oral Squamous Cell Carcinoma: Mechanistic Barriers and Therapeutic Strategies for Durable Immune Reprogramming - Kishore Kumar, Meenakshi Sundaram; Khalid, Jabir Padathpeedika; Martin, Taniya Mary (Asian Pacific Journal of Cancer Biology, 2026)
Objective: Oral squamous cell carcinoma (OSCC) is characterized by a highly complex and immunosuppressive tumor microenvironment (TME) that significantly limits the efficacy and durability of immune-based therapies. Among immune populations, tumor-associated macrophages (TAMs) represent a dominant and functionally plastic cell type that critically influences tumor progression, therapeutic resistance, and immune escape. While macrophage reprogramming toward an anti-tumor (M1-like) phenotype has emerged as a promising therapeutic strategy, durable immunoreprogramming in OSCC remains elusive. Increasing evidence suggests that stromal components of the TME play a decisive role in enforcing macrophage dysfunction and constraining sustained phenotypic conversion. Methods: This review synthesizes current mechanistic insights into how stromal enforcement shapes macrophage dysfunction in OSCC and identifies key barriers to achieving durable immune reprogramming. Results: Metabolic constraints imposed by the stromal milieu further compromise macrophage functionality. Hypoxia-induced HIF-1α stabilization and lactate accumulation drive epigenetic and metabolic reprogramming of TAMs, favoring oxidative phosphorylation and fatty acid metabolism associated with immune suppression. Acidic pH and nutrient deprivation blunt macrophage responsiveness to immunomodulatory agents, limiting the durability of therapeutic reprogramming. In addition, abnormal vasculature and stromal barriers reduce effective drug delivery, leading to heterogeneous and transient macrophage modulation. We highlight the dynamic crosstalk between stromal cells, ECM architecture, and metabolic stressors that collectively undermine sustained macrophage re-education. Conclusion: Furthermore, we discuss emerging therapeutic strategies aimed at overcoming these barriers, including stromal normalization, metabolic rewiring, epigenetic modulation, and nanotechnology-enabled targeted delivery systems.